Risk Factors of Ectopic Pregnancy at Dr. Kariadi Hospital - Kamila Zettira Zahwa; Yuli Trisetiyono; M Besari Adi Pramono; Julian Dewantiningrum (Faculty of Medicine, Diponegoro University, 2025)
Background: Ectopic pregnancy lead to maternal death. There were several risk factors for ectopic pregnancy, including age, IUD, parity, history of ectopic pregnancy, history of pelvic and abdominal surgery, infertility, history of PID, history of abortion, and infertility treatment. This study aimed to prove the correlation between these factors with ectopic pregnancy at RSUP Dr. Kariadi.Objective: This study examines to prove the correlation between these factors with ectopic pregnancy at RSUP Dr. KariadiMethods: This study was an analytical observational study with case control design consisted of 134 samples, divided into ectopic pregnancy (n=67) and threatened abortion as controls (n=67), collected from patient medical records from 2019 – 2024 using purposive sampling. Data analysis was carried out using bivariate analysis with Chi Square & Fisher Exact Test and multivariate analysis with Logistic Regression Test.Results: There were correlation between history of ectopic pregnancy (p = 0,034), history of abortion (p = 0,002), and infertility (p = 0,009) with ectopic pregnancy. Other variables didn’t have significant relationship with ectopic pregnancy (p>0,05). Two risk factors were identified for ectopic pregnancy: history of abortion (p = 0,001; aOR = 3,516; 95% CI 1,632 – 7,577) and infertility (p = 0,005; aOR = 2,913; 95% CI 1,387 – 6,119).Conclusion: There were correlation between history of ectopic pregnancy, history of abortion, and infertility with ectopic pregnancy, while other variables were not related to ectopic pregnancy. History of threatened abortion and infertility were risk factors for ectopic pregnancy.